Autopsy on an Empire : Understanding Mortality in Russia and the Former Soviet Union - Elizabeth Brainerd; David M. Cutler (Institute for the Study of Labor (IZA), 2005)
Male life expectancy at birth fell by over six years in Russia between 1989 and 1994. Many other countries of the former Soviet Union saw similar declines, and female life expectancy fell as well. Using cross-country and Russian household survey data, we assess six possible explanations for this upsurge in mortality. Most find little support in the data: the deterioration of the health care system, changes in diet and obesity, and material deprivation fail to explain the increase in mortality rates. The two factors that do appear to be important are alcohol consumption, especially as it relates to external causes of death (homicide, suicide, and accidents) and stress associated with a poor outlook for the future. However, a large residual remains to be explained.
Keywords: J10; I12; P36; 330; health; mortality; Russia; Eastern Europe; Sterblichkeit; Gesundheitsrisiko; Gesundheitswesen; Alkoholkonsum; Schätzung; Russland; Sowjetunion - Nachfolgestaaten